Global Exponential Stability of Discrete-Time Neural Networks with Time-Varying Delays - S. Udpin; P. Niamsup (Discrete Dynamics in Nature and Society)
This paper presents some global stability criteria of discrete-time neural networks with time-varying delays. Based on a discrete-type inequality, a new global stability condition for nonlinear difference equation is derived. We consider nonlinear discrete systems with time-varying delays and independence of delay time. Numerical examples are given to illustrate the effectiveness of our theoretical results.